Individualizing duration of antibiotic therapy in community-acquired pneumonia. (August 2017) - Aliberti, Stefano; Ramirez, Julio; Giuliani, Fabio; Wiemken, Timothy; Sotgiu, Giovanni; Tedeschi, Sara; Carugati, Manuela; Valenti, Vincenzo; Marchioni, Marco; Camera, Marco; Piro, Roberto; Del Forno, Manuela; et al.
Abstract: International experts suggest tailoring antibiotic duration in community-acquired pneumonia (CAP) according to patients' characteristics. We aimed to assess the effectiveness of an individualized approach to antibiotic duration based on time in which CAP patients reach clinical stability during hospitalization. In a multicenter, non-inferiority, randomized, controlled trial hospitalized adult patients with CAP reaching clinical stability within 5 days after hospitalization were randomized to a standard vs . individualized antibiotic duration. In the Individualized group, antibiotics were discontinued 48 h after the patient reached clinical stability, with at least five days of total antibiotic treatment. Early failure within 30 days was the primary composite outcome. 135 patients were randomized to the Standard group and 125 to the Individualized group. The trial was interrupted by the safety committee because of an apparent inferiority of the Individualized group over the Standard treatment: 14 (11.2%) patients in the Individualized group experienced early failure vs . 10 (7.4%) patients in the Standard group, p = 0.200, at the intention-to-treat analysis. 30-day mortality rate was four-time higher in the Individualized group than the Standard group. Shortening antibiotic duration according to patients' characteristics still remains an open question.